BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
"Current trends in Sugarcane Pathology" Editors. G.P. Rao, A.G. Gillaspie, Jr., P.P. Upadhyaya, A. Bergamin Filho, V.P. Agnihotri and C.T. Chen. International Books & Periodicals Supply Service, 38, Nishant Kunj (Pahari ’Dhiraj Enclave), Pitampura, Delhi-l 10 034, 1994, 472pp, Fully illustrated. Price Rs. 875 (80.00) Biological Control of Social ForestÂ and Plantation Crops Insects. Editor: T.N.Â Ananthakrishnan, Oxford and IBH Publishing Co. Pvt. Ltd., New Delhi, 225pp